Anchor plate effect on the breakout capacity in tension for thin-walled concrete panels. (1st January 2016) - Shin, Jiuk; Kim, JunHee; Chang, Hak-Jong
Highlights: Existing provisions take no account of the effects of anchor plate width. 27 test specimens for anchor plate effects on concrete breakout strength in tension. Concrete breakout strength increases as anchor plate size increase. However, the rate of increase diminishes in very large anchor plates. To propose a simplified model for optimal size of an anchor plate. Abstract: Although provisions available in current design codes that take account of the presence of anchor plates, the existing provisions take no account of the effects of anchor plate size. In this study, the effect of anchor plate size on the concrete breakout strength in tension was evaluated for a single anchor system used in a thin-walled concrete wall panel. Twenty-seven specimens were tested to investigate the effects of anchor plate width and thickness. The test results show that concrete breakout strength is considerably improved with increased anchor plate size, with the rate of improvement diminishing in very large anchor plates. A simplified analytical model was proposed to determine the optimal width and thickness of anchor plates. The predicted optimal values were validated with the test results; the proposed analytical model is capable of determining the proper size of anchor plates in thin-walled concrete panels.